Metaverse (Virtual World) - Abbasi, Mahmoud; Teymouri, Mehrdad (Bioethics and Health Law Journal (BHL), 2025)
The concept of parallel digital realities offering experiences that mirror or transcend the limitations of the physical world has a long history, predating the internet itself. However, advancements in recent decades, such as near-ubiquitous mobile phone adoption and high-speed internet proliferation, have brought the notion of a blended physical and digital reality closer to realization. The Metaverse refers to this convergence, facilitated by computing devices and immersive technologies like virtual reality (VR), augmented reality (AR) and mixed reality (MR). While this vision of a fully realized virtual world remains in its early stages, with its components still under development, the potential of the Metaverse to offer significant opportunities for humanity is clear. However, these opportunities are accompanied by ethical and legal challenges, prompting the critical question of who is responsible for regulating the Metaverse to ensure compliance with ethical and legal frameworks. Undoubtedly, the coming years will necessitate the development of some form of regulation and rule-making to govern human interactions within these digitally connected worlds.